Report on the Academic Symposium: Youth Quotas − The Answer to Changes in Age Demographics? - Igor Dimitrijoski (Intergenerational Justice Review)
The aim of this academic symposium was to provide an answer to the question whether “youth quotas” offer a solution to changes in age demographics and a looming gerontocracy. Based on the premise that young people have the potential to act as change agents, especially with regard to ecological sustainability, it was our aim to stimulate a societal discussion and to raise public awareness on the topic of youth quotas, whilst providing the discussion with a scientific basis.